Mapping of NKp46+ Cells in Healthy Human Lymphoid and Non-Lymphoid Tissues - Tomasello, Elena; Yessaad, Nadia; Gregoire, Emilie; Hudspeth, Kelly; Luci, Carmelo; Mavilio, Domenico; Hardwigsen, Jean; Vivier, Eric (Frontiers in Immunology, 2012)
Understanding Natural Killer (NK) cell anatomical distribution is key to dissect the role of these unconventional lymphocytes in physiological and disease conditions. In mouse, NK cells have been detected in various lymphoid and non-lymphoid organs, while in humans the current knowledge of NK cell distribution at steady state is mainly restricted to lymphoid tissues. The translation to humans of findings obtained in mice is facilitated by the identification of NK cell markers conserved between these two species. The Natural Cytotoxicity Receptor (NCR) NKp46 is a marker of the NK cell lineage evolutionary conserved in mammals. In mice, NKp46 is also present on rare T cell subsets and on a subset of gut Innate Lymphoid Cells (ILCs) expressing the retinoic acid receptor-related orphan receptor t (RORt) transcription factor. Here, we documented the distribution and the phenotype of human NKp46+ cells in lymphoid and non-lymphoid tissues isolated from healthy donors. Human NKp46+ cells were found in splenic red pulp, in lymph nodes, in lungs and gut lamina propria, thus mirroring mouse NKp46+ cell distribution. We also identified a novel cell subset of CD56dimNKp46low cells that includes RORt+ILCs with a lineage-CD94-CD117brightCD127bright phenotype. The use of NKp46 thus contributes to establish the basis for analyzing quantitative and qualitative changes of NK cell and ILC subsets in human diseases.